Valorization of cow manure: Unraveling bacterial community changes driven by vermicomposting and their impact on vermicompost tea production - Uribe Lorío, Lorena (2023)
Vermicomposting is utilized to valorize agricultural residues, including excess manure from dairy farms. The microbiome diversity of vermicompost contributes to its numerous beneficial characteristics. However, it remains unstudied whether teas derived from cow manure vermicompost, even with additives, preserve this microbiome. To respond that, we analyzed the dynamics of bacterial communities in the vermicomposting of precomposted dairy manure, and derived vermicompost teas with and without molasses, using 16S rRNA amplicon sequencing and bioinformatics. Communities of fresh and precomposted manure were dominated by rumen-dwelling and excreta bacteria from the Firmicutes and Bacteroidetes and shared a Bray–Curtis similarity of 71.0% at the genus-level. Precomposting resulted in a decline in the relative abundance of dominant genera, including coliforms. Vermicomposting enhanced diversity and led to a notable shift in the bacterial community composition, as indicated by an 87.0% dissimilarity at the genus-level seen between manure and vermicompost samples. Vermicompost predominantly comprised cellulolytic, nitrogen-fixing, and complex organic compound-degrading bacteria from the Proteobacteria and Bacteroidetes. Production of vermicompost tea did not significantly alter the diversity and bacterial composition of the tea, although pseudomonads and clostridia displayed higher relative abundances. Addition of molasses had a drastic impact, reducing diversity, abundance, and community structure, favoring the proliferation of Acinetobacter and Aeromonas, which collectively accounted for 78.0% of the sequences. In summary, vermicomposting significantly shifted the bacterial community of excreta. The tea retained the diversity and core community of the vermicompost, however, the addition of molasses negatively affected diversity and facilitated the growth of specific gamma-proteobacteria